PENGARUH TEKNIK ASSERTIVE TRAINING TERHADAP KEPERCAYAAN DIRI SISWA KELAS XI SMAN 1 LABUAPI TAHUN PELAJARAN 2023/ 2024: The Effect Of Assertive Training Techniques On Self-Confidence Of Grade XI Students Of SMAN 1 Labuapi In The 2023/2024 - Cabrini Fransiska Jelatu; Reza Zulaifi; M. Zainuddin; I Made Sony Gunawan (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Self-confidence is one of the most important aspects of personality in human life, "self-confidence is one of the factors for someone to be able to consider and make certain decisions themselves" and self-confidence is also a mental attitude of optimism from the child's ability to solve everything and be able to adapt to the situation faced. Therefore, to foster a sense of self-confidence that is very lacking in students, group counseling treatment is given using the Assertive Training Technique. The purpose of this study was to determine the Effect of Assertive Training Techniques on the Self-Confidence of Class XI Students of SMAN 1 Labuapi in the 2023/2024 Academic Year. The design of this study used a one group pre-test-post-test design. The population in this study were classes XI B and XI C with a total of 40 students, and the sample in this study was 9 students who were indicated to have low levels of self-confidence based on the results of the pre-test. Based on the results of data analysis, the t-count value was obtained as (9.756), while for the t-table value with db (N-1) = 9-1 = 8 at a significance level of 5% of (2.306) then Ho is rejected and Ha is accepted. Thus the conclusion obtained in this study: There is an Effect of Assertive Training Techniques on the Self-Confidence of Class XI Students of SMAN 1 Labuapi in the 2023/2024 Academic Year, so it can be concluded that the results of this study are "Significant".